370 Depressive symptoms in the context of Cognitive-Behavioral Therapy for Insomnia, a long-term follow-up study. (3rd May 2021) - Sforza, Marco; Salibba, Andrea; Scarpellino, Alessandro; Galbiati, Andrea; Zucconi, Marco; Casoni, Francesca; Ferini-Strambi, Luigi; Castronovo, Vincenza
Abstract: Introduction: Cognitive-Behavioral Therapy for Insomnia (CBT-I) is considered the first-choice treatment for Insomnia Disease (ID). The bi-directional causal relationship between insomnia and depression is recognized. Aim of our study is to investigate the role of depressive symptoms in predicting CBT-I outcomes, and the effectiveness of the treatment both on insomnia and depression. Methods: 77 ID patients (mean age 38.2±10.4 years, 69.2% females) underwent 7-sessions group CBT-I and were assessed pre- (T0) post- (T1) and at long-term after CBT-I (T2=7.6±1.6 years after treatment). The primary outcomes are Insomnia Severity Index (ISI) and Sleep Diary parameters. The secondary outcome is Beck Depression Inventory-II (BDI). Patients were divided in two groups according to BDI baseline score (≥14): depressive (D) vs non-depressive (ND). Results: All patients showed significant improvements at ISI score at T1 that were maintained at T2 (T0=16.2±4.8 vs T1=8.2±4.5 vs T2=10.0±6.1;p<0.001). Also Sleep Diary parameters (sleep latency, wake after sleep onset and sleep efficiency) showed significant improvement at T1 (p<0.001). Moreover all patients showed improvements of depressive symptoms at T1 that were maintained at T2 (T0=10.8±6.8 vs T1=6.2±5.5 vs T2=8.2±6.6; p<0.001). Indeed, if 29.3% if ID patients at T0 presented clinically significant depressive symptoms (BDI≥14), only 9.7% at T1 and 20.5% at T2. Nevertheless, we found an interaction between ISI along time (T0-T1-T2) and D vs ND group membership (ISI_TREAT*BDI_BL_GROUP Sig=p<0.05). In other words, group D patients at baseline showed a worsening of insomnia symptoms at the long-term evaluation (T2). Conclusion: CBT-I showed improvements both in insomnia and in depressive symptoms at the end of treatment that are maintained at long-term (7.6yrs after treatment). Nevertheless, clinically significant depressive symptoms at the baseline predicted a worsening of insomnia at the long-term evaluation. This could suggest the need of a more frequent follow-up evaluation of CBT-I efficacy in those patients presenting depressive symptoms at the baseline. Support (if any): None